A discourse analysis of print media constructions of 'Muslim' people in British newspapers - Nanabawa, Sumaiya (Rhodes University, Faculty of Humanities, Department of Psychology, 2013)
This research study aimed to examine how the identity of ' Muslim' people is constructed in British print media today, and whether or not these constructions promote or undermine a xeno-racist project. The research draws on the idea that identity is partly constructed through representation, with an emphasis on how language can be used to construct and position people in different ways. Using a social constructionist paradigm, the study further considers the role that print media has in providing a discursive field within which the construction and reproduction of racist attitudes and ideologies in contemporary global society can take place. Sixty-five newspaper articles were selected from the online archives of British newspapers, The Guardian and The Daily Telegraph using systematic random sampling. These were analysed using the six stages of Foucauldian discourse analysis outlined by Carla Willig. To provide a more fruitful account, the analysis also incorporated the methods of Potter and Wetherell whose focus is on the function of discourse, as well as van Langenhove and Harre's focus on subject positioning, and Parker's use of Foucauldian analysis which looks at power distributions. The analysis revealed that Muslims are discursively constructed as a direct politicised or terror threat, often drawing on discourses of sharia law, and Muslim-Christian relationships. They are also constructed as a cultural threat, drawing on discourses of isolation, oppressed women, the veil/headscarf, identity, visibility and integration. The analysis also showed some variation in constructions, and these extended from the racialization of Muslims to showing the compatibility between Islamic and western values. This study discusses the form these different constructions take and the possible implications these constructions might have in contributing toward a prejudiced and largely negative image of Islam and Muslims.
Keywords: Muslims -- Great Britain -- Public opinion; Islam -- Great Britain -- Public opinion; Racism in mass media; Mass media -- Political aspects -- Great Britain; Mass media -- Social aspects -- Great Britain; Journalism -- Social aspects; Journalism, Commercial -- Great Britain